Pedagogue and scholar S. Z. Katsenbogen and Sverdlovsk State Pedagogical Institute in 1935–1946 - Popov, Mikhail V.; Suvorov, Maksim V. (Journal of the Belarusian State University. History, 2020)
The history of higher education in Russia and the near abroad is inseparably connected with the activity of higher education institutions administrators and their teaching and scholarly activity. They were the people who implemented the government policy in the sphere of higher education. In the 1920–40s, the academic and scholarly activity in the Soviet higher education institutions depended, to a large extent, on the change of the socio-political situation in the country. This was reflected in the fates of those who headed higher school administrations. The authors’ study of political and professional activity of higher school administrators can provide an objective assessment of their activity as managers, pedagogues and scholars. In this regard, the study the life of Solomon Zakharovich Katsenbogen – a sociologist, philosopher, pedagogue and higher school administrator becomes especially interesting and urgent. The 100th anniversary of the foundation of the Belarusian State University and the 90th anniversary of the foundation of Sverdlovsk State Pedagogical Institute (now Ural State Pedagogical University) can also serve as very good reasons for the publication of this material. The article deals with the work of S. Z. Katsenbogen under the conditions of the change in the socio-political life taking place in the USSR in the second half of the 1930s – 1940s. It is the first attempt to study his professional activity as a lecturer and administrator at the higher education institutions of the Urals, and first of all at Sverdlovsk State Pedagogical Institute. The article analyzes the political leanings and behavior of S. Z. Katsenbogen under the conditions of the Stalinist regime, which was responsible for false allegations against him: suspiciousness and distrust in relation to colleagues and slowdown in scholarly activity because of fear of criticism for political reasons. At the same time, the authors make a conclusion about a positive contribution of the professor to the improvement of the functioning of higher schools in the Urals: a new approach to the organization of planning of scientific activity of higher education institutions, the creation of the system of control of the conduct of lectures and tutorials by teachers on the part of the heads of departments and higher school administration. Under the conditions of mass repression, S. Z. Katsenbogen did not become a slanderer and careerist; he sincerely believed that due to his hard work and moral behavior, he would eventually have his party disciplinary penalties withdrawn. His colleagues – pedagogues of the higher education institutions of the Urals – also believed in this, but he never achieved rehabilitation from the party officials. The fate of professor Katsenbogen was to a great extent highly typical of the historical situation in the country during Joseph Stalin’s rule. In this perspective, the aim of the article is to reveal the consequences of the impact of political factors and peculiarities of the social life of the period of 1935–1946 on the activity of the higher school administrator, scholar and pedagogue. On the other hand, the authors tried to carry out their investigation within the framework of the historical-anthropological approach, in which a person functions as an active historical subject, as a historical factor, and as a bearer of a political culture and mentality. To achieve the aim and the tasks of the study, it is important to expand the investigation source base now as a result of publicizing a number of archival materials previously inaccessible for historians.
Keywords: higher education; Ural; the second half of the 1930s – the first half of the 1940s; political views; scientific and teaching activities; university manager; scientist; teacher; ideological control; party-Soviet leadership; Stalinist repression